„Kochana Joanno” – dziennik pisarski Oli Watowej - Anna Gawryś-Mazurkiewicz (Napis)
The article is composed of two complementary parts: the reworked (according to the rules of genetic criticism) and annotated, previously unpublished home manuscript by Ola Watowa, found in an archive, and an introduction containing a philological-theoretical commentary. The draft, written up over the course of several winter days in 1970 deserves attention for many reasons: 1. Its value is that of testimony, as it is a record of personal reflections of the author, and constitutes an important part of her biography, 2. It documents the origins of the recollective book Wszystko co najważniejsze. Rozmowy z Jackiem Trznadlem [All that is most important. Conversations with Jacek Trznadel], 3. It presents Watowa in a light that is different than usual – it shows the process of her becoming an independent author, 4. It is interesting in a formal sense – it opens with a message to the addressee which suggests that we are dealing with a draft copy of a letter, and then morphs into a writer’s journal. Joanna, to whom the first words are addressed, turns out to be merely an artistic creation of Watowa, which is why this article pays particular attention to the genre status of the text.